Pengaruh Gaya Kepemimpinan terhadap Kepuasan Kerja Karyawan pada KPKNL Manado - Kawengian, Deddy; Areros, William Agustinus; Wonokh, Jan (JURNAL ADMINISTRASI PUBLIK, 2015)
This study aims to: To determine the influence of significant between leadership styleon employee job satisfaction the State Property Office and Auction Manado. This study usedquantitative descriptive method using a simple correlation analysis. Measurement of thepopulation in this study are employees of the State Property Office and Auction Manadototaling 40 people.The result of analysis can product moment coefficient that is equal to 0.718 whichshows the significant correlation or relationship between leadership style on employee jobsatisfaction.With the results of this means there is a leadership style had a strong influence andsignificant impact on employee satisfaction the State Property Office and Auction ManadoKeywords: leadership style, job satisfaction